The Histopathology of Anorectal Neisseria gonorrhoeae Infection. Issue 5 (8th August 2022) - Cox, Brian K; Larson, Brent K; Hutchings, Danielle A; Morgan, Margie; Balzer, Bonnie L; Waters, Kevin M
Abstract: Objectives: Neisseria gonorrhoeae infection of the anorectal tract is often asymptomatic and infrequently biopsied, but pathologists can be tasked with identifying the histologic features of possible infection. The study was undertaken to better characterize clinical and morphologic features of confirmed anorectal gonococcal infection. Methods: From 2011 to 2020, 201 positive gonococcal nucleic acid amplification testing samples from 174 patients collected from the distal colorectum and/or anus were matched to eight patients with concurrent biopsy specimens of the distal anorectum. Complete demographic, clinical, and infectious information was collected for each biopsied patient. The histomorphologic features of each biopsy were systematically tabulated. Results: All eight gonococcal cases were obtained from men who have sex with men. Each case showed at least mild acute inflammation with moderate activity identified in one case with concurrent cytomegalovirus infection. Intense lymphoplasmacytic infiltration was not commonly seen (two of eight). Half of the cases showed mucosal ulceration, and seven of eight cases demonstrated lymphoid aggregates. Conclusions: The microscopic features are mild compared with other well-described types of infectious proctitis, with most cases displaying mild acute inflammation and scattered lymphoid aggregates. These findings highlight the importance of obtaining a complete patient history and recommending additional infectious workup even when only subtle changes are present.